Muscle power performance in parabadminton athletes: Influence of classification, impairment type, and anthropometric factors - Oliveira, S. F. M.; Oliveira, J. I. V.; Alves, J. F. V. V.; Lourenço, T.; Haiachi, M. C.; Felder, H. (International Journal of Sports Science & Coaching, 2025)
This study compared muscle power indicators among Parabadminton athletes and identified the contributions of anthropometric factors and types of impairment. Seventy-four athletes, comprising 47 in the ST group (STANDING-ST, SL3, SL4, SU5, and SH6) and 27 in the WH group (WHEELCHAIR-WH, WH1 and WH2), underwent muscle power tests. The ST group performed three countermovement jumps (CMJ), measuring maximum height (CMJMax, cm), percentage of maximum height (%CMJMax), power (PO, W), and reactivity index (RI). The WH group performed three medicine ball throws, with the best throw (BEST, m), percentage of the best throw (%DIFMax), absolute power (PO, W), and relative power (PO, W/kg) measured. MANCOVA comparison tests were conducted (p < 0.05). For PO (W), SU5 athletes exhibited higher values than SL3 and SH6 athletes (1920 W vs. 1020 W and 814 W), and SL4 athletes showed higher values than SL3 and SH6 athletes (1604 W vs. 1020 W and 814 W). In the WH group, BEST and PO (W) were superior for the WH2 class (5.27 m vs. 6.40 m; and 10.5 W vs. 12.8 W). In the ST group, type of impairment and body mass index significantly influenced CMJMax (F = 522.837, p = 0.028) and RI (F = 561.829, p = 0.023), while in the WH group, the sport classes influenced BEST (F = 8.410, p = 0.008) and PO (W) (F = 96.181, p = 0.005), with height affecting BEST (F = 19.154, p < 0.001) and PO (W) (F = 191.539, p < 0.001). It can be concluded that type of impairment, body mass index, and height influence the best indicators of muscle power regardless of the classes analyzed.